SÍNDROME DE PLATIPNEA- ORTODEOXIA COMO PRESENTACIÓN DE TROMBOEMBOLISMO PULMONAR - Acuña Feoli, José Alonso (2011)
The diagnosis of Platypnea-Orthodeoxia Syndrome is mainly clinical and should be confirmed by laboratory tests. Because of this fea-ture, the clinical suspicious is the most importantfact in the assessment of the patient and the physician should perform an exhaustive clinicalhistory as well as physical examination. Theorigin of this syndrome relies in a defect in theventilation/perfusion ratio and once identified,the diagnostic assessment should be oriented toestablish the underlying cause and the most appropriate treatment. For this article, a bibliographic revision wasperformed about platypnea/orthodeoxia syndrome, because of the case of a 73 years oldfemale, who came to our hospital with a suspected pulmonary embolism.